Pengaruh Penggunaan Media Wordwall Terhadap Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Pancasila Di Kelas 4 A SDN 1 Pabedilankaler - Rachmi, Ayulia; Darmini, Mimin; Widiawati, Hema (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study was conducted to find out "The Effect of the Use of Wordwall Media on Students' Learning Interest in Pancasila Education Subjects in Class 4 A SDN 1 Pabedilankaler". This research includes quantitative research with a pre-experimental method with a One-Group Pretest-Posttest Design research design. The sample amounted to 30 students. The data collection techniques in this study are in the form of observation, pretest-posttest, and questionnaire. The instrument test in this study uses validity and reliability tests. The prerequisite test in this study is the Shapiro-Wilk normality test. The hypothesis test uses the Paired Simple T-test to see the significance of the influence of wordwall media on learning interest and an N-Gain test is carried out to measure the level of effectiveness of the media used on learning interest. Based on the results of the research, the observation data that has been carried out shows that the process using wordwall media is relatively good. Based on the results of the questionnaire regarding learning interest before being given treatment, an average score of 55.17 was obtained, after being given treatment, an average score of 60.40 was obtained. It can be described that students' interest in learning has increased after being given media treatment. The increase in learning interest is evidenced by an average increase of 5.23. Based on the results of the pretest posttest from the Paired Simple T-test sample test, it is known that the Sig result is 0.000 < 0.05, according to the decision-making criteria, Ho is rejected and Ha is accepted. The average value obtained from the N-gain score test and N-gain percent was 0.6933. Based on the qualifications, the N-gain test is included in the medium category. It can be concluded that wordwall media has an effect on students' interest in learning Pancasila Education in grade 4 A SDN 1 Pabedilankaler.